Peran Tenaga Kesehatan Dan Dukungan Keluarga Terhadap Pengendalian Perilaku Merokok Pada Lansia Perempuan Di Dataran Tinggi Dieng - Widiyaningsih, Dwi; Setyowati, Rustiana (STIKES Yayasan RS.Dr.Soetomo, 2021)
Smoking is the cause of nearly 90% of lung cancers, 75% of chronic obstructive pulmonary disease (COPD), and it is also the cause of 25% of heart attacks (Tobacco Atlas). Our nation has not lost its mind in controlling smoking behavior, various efforts have been made ranging from making laws, regulations and policies to even taking a comprehensive approach to the family as a long-handed health program besides being carried out by health workers in their efforts to control smoking behavior, as happened in Dieng plateau where 41% of active smokers are the elderly and what is even more astonishing 29.5% are elderly women who occupy important and respected roles in society because of their high social status and ancestral culture, not to mention the position of women as mothers in the household also becomes the key in creating the next healthy generation so that the family approach is the right strategy in implementing health programs. This study is to identify the effect of the role of health workers and family support on the control of female elderly smokers in the Dieng highlands. This type of quantitative research with cross sectional approach. The study population was 125 elderly who were all sampled (total sampling technique). Data analysis used the test (Kendall tau) and multiple linear regression, with the value of the Kendall Tau test, namely (0.001 <0.005) and (0.000 <0.005) which means that there is a significant influence significant, while the results of the F test count 38.849> F table 3.07 with a significance level of 0.000 (ρ <0.005). So it can be concluded that the better the role of health workers and family support, the better the smoking behavior control. The suggestion for future researchers is to measure the level of nicotine dependence in smokers to determine the appropriate counseling therapy.